The effects of two different antioxidant combinations on sperm parameters. Issue 4 (November 2022) - Yaris, Mehmet; Akdogan, Nebil; Öztürk, Murat; Bozkurt, Aliseydi; Karabakan, Mehmet
Background: Studies demonstrate that getting antioxidants in the course of treatment has a positive impact beneficial effect on fertility, especially on the quality of sperm. Because of that reason antioxidants are recommended as a potentially influential treatment for infertility in men. However, it is argued that this treatment is not based on sufficient evidence and has no effect on the rate of healthy pregnancy. Objective: In this study, two different antioxidant combinations with different doses and contents were evaluated in terms of their effect on sperm parameters. Materials/methods: A total of 122 patients diagnosed with idiopathic infertility were enrolled in our multicenter study. The patients were divided into two different groups: The first group used a combination 2 × 1 sachet form (l -carnitine 1 g, acetyl-l -carnitine 0.5 g, fructose 1 g, citric acid 0.50 mg, selenium 50 µg, coenzyme Q10 20 mg, vitamin C 90 mg, zinc 10 mg, folic acid 200 µg, and vitamin B12 1.5 µg) and the second group used a combination tablets form 2 × 1 (l -carnitine 500 mg, selenium 50 µg, coenzyme Q10 20 mg, vitamin C 60 mg, zinc 15 mg, folic acid 400 µg, vitamin E, and ginseng 15 µg) for 6 months. The total semen volume, the total sperm number, sperm concentration, sperm motility, and lastly morphological findings of the patients were compared at the end of 6 months. Results: The mean age of the patients participating in the study was 30.8 ± 6.05 years. No significant difference was found between the two groups in terms of baseline sperm count. There was a significant difference between the baseline and sixth-month values of the patients using both combinations. However, no significant statistical difference was found between the groups according to the sixth-month data. The combinations of both antioxidants had a positive effect on sperm parameters, and the use of different doses and contents had a similar effect. Conclusion: Both antioxidants respectively had a positive effect on sperm parameters and also the use of different doses and contents had a similar effect.